Respuesta :
Ksp, the product of solubility constant is given by the product of the concentrations in the equilibrium of the species on the right hand of the equillibrium reaction, each raised to a power that is its coeffiicient in the equillibrium reaction.
So you must start by writing the equilibrium reaction:
Fe(OH)3 (s) ----> Fe(3+) aq + 3 (OH-) aq
Now you can state the formula for the Ksp
=> Ksp = [Fe (3+) aq] [OH-]^3
So, the answer is the third option of the list.
So you must start by writing the equilibrium reaction:
Fe(OH)3 (s) ----> Fe(3+) aq + 3 (OH-) aq
Now you can state the formula for the Ksp
=> Ksp = [Fe (3+) aq] [OH-]^3
So, the answer is the third option of the list.